Carbon Footprint Analysis and Tourist Satisfaction of 4As at an Ex-situ Conservation Institution - Hasibuan, Ratna Sari; Soekmadi, Rinekso; Purnomo, Herry; Mulyono, Nur Budi (Jurnal Sylva Lestari, 2025)
Taman Safari Indonesia (TSI), an ex-situ conservation institution in Puncak, Bogor, has developed the 4A framework to attract more tourists and enhance visitor satisfaction and loyalty, while increasing visits revenue. It has also raised the carbon footprint of tourist transportation. This study aims to analyze the vehicle emissions of tourists and their satisfaction with 4A components to predict the likelihood of repeat visits and the subsequent rise in carbon emissions. Emissions were calculated using the IPCC 2006 Guidelines (Tier 2), and the relationship between tourist satisfaction and loyalty was assessed using the structural equation model partial least squares (SEM-PLS) method. The results indicated that CO2 emissions from tourist vehicles during holidays reached 1,482,261.96 g.CO2/h, significantly higher than the 552,732.81 g.CO2/h recorded on weekdays. The analysis also revealed that tourist satisfaction and loyalty towards the 4A components significantly positively impacted the intention to revisit, as demonstrated by the T-statistics of 5.437 and P-values of 0.000, where the more satisfied the tourists are, the more loyal they are to return to TSI. Keywords: carbon footprint, IPCC, loyalty, satisfaction, SEM-PLS